Issue evolution : race and the transformation of American politics - Carmines, Edward G.; Stimson, James A. (Princeton, N.J. : Princeton University Press, 1989)
To test their theory of how issues can reshape the political system, Carmines and Stimson examine the impact of race on American politics in recent decades. They focus on presidential campaigns, congressional votes, party activists, and mass attitudes; and develop their alternative to realignment theory.
Cover Page -- Half-title Page -- Title Page -- Copyright Page -- Contents -- List of Figures -- List of Tables -- Preface -- Acknowledgments -- 1. The Dynamics of Issue Evolution -- 2. The Politics of Race: From Roosevelt to Reagan -- 3. The Politics and Policy of Race in Congress -- 4. Political Activism and the Party System -- 5. The Ideological and Partisan Transformation of Racial Issues -- 6. Modeling Change in Mass Identification -- 7. On the Structure and Sequence of Issue Evolution -- 8. Racial Issue Evolution: Strategy, Chance, and Opportunity -- Bibliography -- Index
Bibliography: p. 199-207.
Includes index.
Replacement copy (copy 3) for the general collection.
Description based on print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: Universidad Sergio Arboleda; United States -- Race relations -- Political aspects; African Americans -- Politics and government; United States -- Politics and government -- 1945-1989.; Voting -- United States -- History -- 20th century; Noirs américains -- Politique et gouvernement; Vote -- États-Unis -- Histoire -- 20e siècle.; États-Unis -- Relations raciales -- Aspect politique; États-Unis -- Politique et gouvernement -- 1945-1989.; African Americans -- Politics and government; Politics and government; Race relations -- Political aspects; Voting; United States; Politik; Rassenfrage; Rassenpolitik; USA; 1900-1999; Geschichte 1945-1989; Race relations; United States; History